Corporate Efficiency, Credit Status and Investment - Manzur Quader; Karl Taylor (Institute for the Study of Labor (IZA), 2014)
Using a panel of 1122 UK firms listed on the London Stock Exchange over the period of 1981 to 2009, endogenous switching regression models (SRM) incorporating a predicted corporate efficiency index are estimated in this paper in an effort to clarify the role of cash flow in examining the impact of capital-market imperfections. It is revealed that a firm's constrained credit status changes with the improvement of its efficiency. The results further reveal that financially constrained firm's investment is comparatively more sensitive to cash flow, but this sensitivity is negatively and significantly related with corporate efficiency. These results point to the fact that high investment sensitivity to cash flow may not be solely driven by measurement error in investment opportunity, but may still be interpreted as a consequence of imperfect substitutability between internal and external financing arising from the capital market imperfections.
Keywords: C34; D92; G14; L21; 330; asymmetric information; financial constraints; switching regression